2008
DOI: 10.1111/j.1464-5491.2008.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

New potential treatments for protection of pancreatic B‐cell function in Type 1 diabetes

Abstract: Type 1 diabetes mellitus results from the progressive and specific autoimmune destruction of insulin-secreting pancreatic B-cells, which develops over a period of years and continues after the initial clinical presentation. The ultimate goal of therapeutic intervention is prevention or reversal of the disease by the arrest of autoimmunity and by preservation/restoration of B-cell mass and function. Recent clinical trials of antigen-specific or non-specific immune therapies have proved that modulation of islet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Due to the pathogenic complexity of this disease, development of an effective method for late prevention or reversal post-onset of the disorder has been remarkably challenging [1]. Although recent studies have shown promising results in terms of reversing type 1 diabetes, many of these treatments can lead to detrimental side effects [2][3][4]. As such, the exploration of therapies with more tolerable adverse event profiles is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the pathogenic complexity of this disease, development of an effective method for late prevention or reversal post-onset of the disorder has been remarkably challenging [1]. Although recent studies have shown promising results in terms of reversing type 1 diabetes, many of these treatments can lead to detrimental side effects [2][3][4]. As such, the exploration of therapies with more tolerable adverse event profiles is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although in some patients, these therapies could induce clinical remission (i.e., relinquish the need for exogenous insulin), this effect was only transient, and lasting, at most, until near time when therapy was stopped. Although these therapies are considered too toxic for an indefinite use in those with newly diagnosed type 1 diabetes (especially young children), these studies did provide a proof-in-principle that if potent, yet safe and well tolerated, immune modulatory therapy was started soon after initial diagnosis, enough residual b-cells could be rescued to allow permanent reversal (or cure) of this disease [9,30].…”
Section: Type 1 Diabetes: Firmly An Autoimmune Diseasementioning
confidence: 95%
“…Realizing that type 1 diabetes is an immune-mediated disorder, in the 1980s and 1990s, several clinical studies [9,30,[42][43][44][45][46][47] investigated the effect of potent immune Type 1 diabetes research Rigby 133 suppressants, including cyclosporine, azathioprine, prednisone and antithymocyte globulin, on newly diagnosed diabetes. Although in some patients, these therapies could induce clinical remission (i.e., relinquish the need for exogenous insulin), this effect was only transient, and lasting, at most, until near time when therapy was stopped.…”
Section: Type 1 Diabetes: Firmly An Autoimmune Diseasementioning
confidence: 99%
“…and non-calcineurin inhibitors (e.g., rapamycin, MMF, etc.) seem indispensable at this stage [81]. 3.…”
Section: Treatmentmentioning
confidence: 98%